PERUMUSAN KEUNGGULAN BERSAING YANG BERKELANJUTAN MENGGUNAKAN RESOURCE BASED VIEW PADA TOKO PERLENGKAPAN BAYI X DI KOTA GRESIK - Rachma, Savira Uchtia (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
In formulating a strategy, the company pays attention to the external environment and the surrounding internal environment. Changes in the external environment bring both opportunities and threats to the company. To overcome this, companies must be able to utilize the resources and capabilities they have. The uniqueness possessed by these resources and capabilities will produce a differentiator between the company and its competitors. In the baby equipment retail industry, where the number of competitors is very large, companies need competitive advantages in order to be able to win the competition. Baby equipment shop X as one of the companies in the retail sector of baby equipment in Gresik City needs to understand its resources and capabilities in order to be able to overcome threats such as competition and other environmental changes, as well as take advantage of existing opportunities to bring companies to obtain maximum profits and achieve sustainable competitive advantage. advantage (SCA). This study aims to analyze the internal side of the baby equipment retail company X through a Resource Based View (RBV) approach in order to achieve a sustainable competitive advantage (SCA) by using the VRIO framework as an analytical tool. Keywords: Resource Based View (RBV); VRIO framework; technology; resources and capabilities; sustainable competitive advantage (SCA).